Health Professionals Perception of Enhanced Recovery After Surgery: A Scoping Review - Rosyidah, Rafhani (W.B. Saunders, 2022)
Purpose: The Enhanced Recovery After Surgery (ERAS) program is currently poorly implemented by healthcare workers. Furthermore, several inhibiting and supporting factors for this implementation have been discovered to influence healthcare workers’ perception of the program. This study aims to investigate the perception of healthcare workers regarding the ERAS program. Design: A scoping review in a systematic manner. Methods: A systematic search was performed using six databases: PubMed, ScienceDirect, SCOPUS, EBSCO, Proquest, and Sage Journals, from August 2011 to August 2021. The data was extracted using an excel worksheet, and the results obtained were presented descriptively. Findings: This study selected a total of 10 articles, where both qualitative and quantitative methods were used to discuss the perceptions of healthcare workers about ERAS. Conclusions: Based on this study's findings, not all healthcare workers have a good perception of ERAS. The implementation of ERAS is often hindered by several factors, including resistance to change and lack of knowledge about the program. However, good teamwork and support from hospital management can support the program's implementation.